2005
DOI: 10.1002/ejoc.200500205
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine in Peptide Design and Protein Engineering

Abstract: The use of fluorine has become well established in the analysis of protein structure and function, e.g. in tools such as 19F NMR spectroscopy. The application of the unique electronic properties of this element for the structural and chemical modification of peptides and proteins emerged as a promising approach. However, the influences of amino acid fluorination on side‐chain interactions in proteins are still controversially discussed. The systematic investigation of the interaction properties of fluoroalkyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
132
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(139 citation statements)
references
References 164 publications
3
132
0
1
Order By: Relevance
“…Fluorinated compounds are more hydrophobic than hydrogenated compounds of equal carbon number (4,5,(17)(18)(19)(20)(21), and the increase in hydrophobic character of fluorocarbons has been ascribed to their increased molecular size (18,56). This interpretation appears to be consistent with the observation that the melting temperature of A1-Tfl is 13°C higher than that of A1-Leu (11), while T m for A1-Hil is increased by 17°C in comparison to A1-Leu.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Fluorinated compounds are more hydrophobic than hydrogenated compounds of equal carbon number (4,5,(17)(18)(19)(20)(21), and the increase in hydrophobic character of fluorocarbons has been ascribed to their increased molecular size (18,56). This interpretation appears to be consistent with the observation that the melting temperature of A1-Tfl is 13°C higher than that of A1-Leu (11), while T m for A1-Hil is increased by 17°C in comparison to A1-Leu.…”
Section: Discussionsupporting
confidence: 72%
“…Fluorinated amino acids have drawn special attention (4-16) because of the unusual solubility properties of fluorinated hydrocarbons. Several independent studies have shown that fluorination of coiled-coil and helix-bundle proteins leads to enhanced stability with respect to thermal or chemical denaturation (6-12), an effect attributed to the hyper-hydrophobic and fluorophilic character of fluorinated amino acid side chains.Although both classes of compounds are hydrophobic, hydrocarbons and fluorocarbons differ in important ways (17)(18)(19)(20)(21)(22). The high electronegativity of fluorine renders the C-F bond both strongly polar and weakly polarizable (17,21,22).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The non-epimerizable compound 6 should be a suitable model to study the relationship between the stereochemistry and the biological activities of 4. Introduction of fluorinated amino acids such as 6 into peptides often changes the original conformation and biological properties [12]. Moreover, clinical application of BMS-204532 (Maxipost, 7) as a potassium channel opener [13] further encouraged us to pursue the synthesis the fluorinated tryptophan analog 6 as a potential building block for drug development.…”
Section: Introductionmentioning
confidence: 99%
“…8 The multi-faceted impact of fluorinated amino acids on peptides and proteins was discussed in a recent review. 9 From a pharmaceutical chemistry standpoint, fluorinated amino acids can be used as pharmacokinetic modulators (via prolonged in vivo half-life, t ½ ) and reporters (via 19 F NMR) for peptide-based pharmaceuticals. 10 Several methods have been developed for site-specific incorporation of fluorinated amino acids into peptides or proteins, including both solid-1, 2, 3 and solution- 7,11 phase chemical synthesis, protease-catalyzed synthesis 12 and in vivo bio-synthesis.…”
Section: Introductionmentioning
confidence: 99%